THREE-FOLD PRESENTATION OF AN ACCOUNTING PROBLEM. - Pilcher, D. J. (The Accounting Review, 1933)
This article discusses the three-fold presentation of an accounting problem. The obstacles that confronts a layman eager to attain a good understanding of principles of accounting are limited knowledge of applied business practices, a group of terms, easy of spelling and pronunciation, but difficult of comprehension, a particular mechanism of thought, based upon certain phases of logic and an unavoidable drawing together of the conclusion of a selected example in relation to the probable past and future financial history of the business unit. The principal divisions of a plan proposed consist of – a statement of fact, an accounting interpretation of two parts, journalized form and T-form and observations as may be set out in trial-balance form. The consideration of the three-fold presentation of an accounting problem may depend upon its usefulness as a teaching device in bringing together in concise form certain implied facts and business and accounting relationships and offering a unique method of reviewing in a progressive manner basal principles and materials which form the essence of instruction.